Social inequalities in diabetes incidence and quality of care: results from a cohort study in the Lazio region, Italy - Marina Davoli; Silvia Cascini; Nera Agabiti; Giulia Cesaroni; Teresa Dalla Zuanna; Chiara Sorge; Angelo Nardi (BMJ Open)
Objectives Socioeconomic disparities in diabetes incidence vary across countries and geographical areas. In addition, once diabetes is diagnosed, further disparities can arise during the whole care process. This study aims to evaluate disparities in incidence and glycated haemoglobin (HbA1c) testing in Central Italy.Design Cohort study.Setting Lazio region, Italy.Participants We used the Lazio Region Longitudinal Study, which is the 2011 census cohort of all residents followed from January 2012 to December 2022. We selected 2 912 539 diabetes-free individuals aged 35–90 years at baseline (54% women). We used educational attainment as the indicator of socioeconomic position and place of residence and birth citizenship as possible confounders.Main outcome measures We identified incident cases of type 2 diabetes from 2012 to 2022 using health databases. We searched for an HbA1c test in the 13 months following case identification. We used Cox proportional hazard models and logistic regression models stratified by sex to study disparities in diabetes incidence and HbA1c testing, respectively.Results We identified 192 268 new cases (49% women). We found incidence disparities, with the lowest educational level showing a risk that is twice or more than the highest in men (HR 2.03, 95% CI 1.98 to 2.08) and women (HR 2.32, 95% CI 2.26 to 2.39), respectively. Disparities were less pronounced in the older groups. Fewer than 60% of individuals across all educational levels had at least one HbA1c test. Compared with those with university degrees, people with the lowest education showed a higher probability of being tested for HbA1c in men (OR 1.56, 95% CI 1.48 to 1.64) and women (OR 1.62, 95% CI 1.53 to 1.72).Conclusions We found inequalities in diabetes incidence in both sexes, mainly among younger groups. The highly educated were less likely to be tested for HbA1c, although different private sector utilisation could have influenced this result.